Sisters of the lost nation - Medina, Nick (Berkley, 2023)
"A young girl hunts for answers about a string of disappearances, all while being haunted herself in this heart-pounding thriller with a mythological twist, from debut author Nick Medina. Anna Horn is always looking over her shoulder. For the bullies who torment her, for the entitled visitors at the reservation's casino... and for the nameless, disembodied entity that stalks her every step--an ancient tribal myth come to life, one that's intent on devouring her whole. With strange and sinister happenings occurring around the casino, Anna starts to suspect that not all the horrors on the reservation are old. As girls begin to go missing and the tribe scrambles to find answers, Anna struggles with her place on the rez, desperately searching for the key she's sure lies in the legends of her tribe's past. When Anna's own little sister also disappears, she'll do anything to bring Grace home. But the demons plaguing the reservation--both old and new--are strong, and sometimes, it's the stories that never get told that are the most important"--